Associations between antimony exposure and glycated hemoglobin levels in adolescents aged 12–19 years: results from the NHANES 2013–2016 - Feng, Baoying; Tang, Peng; He, Sheng; Peng, Zhenren; Mo, Yan; Zhu, Liqiong; Wei, Qiufen (Frontiers in Public Health, 2024)
Objective: This study aimed to investigate the association between antimony (Sb) exposure and glycated hemoglobin (HbA1c) levels in adolescents. Methods: A cross-sectional study of 751 adolescents aged 12-19 years was conducted via the National Health and Nutrition Examination Survey (NHANES, 2013–2016). Survey-weighted linear regression and restricted cubic spline (RCS) analyses were applied to evaluate the relationship of urinary Sb exposure with HbA1c. Results: A significant relationship was observed between urinary Sb concentrations and HbA1c levels (percent change: 0.93; 95% CI: 0.42, 1.45) after full adjustment. After converting urinary Sb levels to a categorical variable by tertiles (T1–T3), the highest quantile was associated with a significant increase in HbA1c (percent change: 1.45; 95% CI: 0.38, 2.53) compared to T1. The RCS models showed a monotonically increasing relationship of urinary Sb with HbA1c. Subgroup analyses revealed a sex-specific relationship between urinary Sb exposure and HbA1c with a significant positive association in males and a non-significant positive association in females. Sensitivity analyses further confirmed the relationship between urinary Sb and HbA1c, even after excluding participants who were overweight or obese (percent change: 1.58%, 95% CI: 0.88, 2.28) and those with serum cotinine levels ≥ 1 ng/mL (percent change: 1.14%, 95% CI: 0.49, 1.80). Conclusion: Our findings indicated that increased Sb exposure may correlate with higher HbA1c levels, especially in male adolescents. More studies are needed to further explore and validate the potential mechanisms.